A Review on the Potential Use of Medicinal Plants From Asteraceae and Lamiaceae Plant Family in Cardiovascular Diseases - Michel, Jennifer; Abd Rani, Nur Zahirah; Husain, Khairana (Frontiers in Pharmacology, 2020)
Cardiovascular diseases are one of the most prevalent diseases worldwide and its rate of mortality is rising annually. In accordance with the current condition, studies on medicinal plants upon their activity on cardiovascular diseases are often being encouraged to be used in cardiovascular disease management, due to the availability of medicinal values in certain dedicated plants. This review was conducted based on two plant families which were Asteraceae and Lamiaceae to study on their action in cardiovascular disease relieving activities, to review the relationship between the phytochemistry of Asteraceae and Lamiaceae families and their effect on cardiovascular diseases, and to study their toxicology. The medicinal plants from these plant family groups are collected based on their effects on the mechanisms that affect the cardiovascular-related disease which are an antioxidant activity, anti-hyperlipidemic or hypocholesterolemia, vasorelaxant effect, antithrombotic action and diuresis effect. In reference to various studies, the journals that conducted in vivo or in vitro experiments were used to prove the specific mechanisms, are included in this review. This is to ensure that the scientific value and the phytochemicals of the involved plants can be seen based on their activity. As a result, various plant species from both Asteraceae and Lamiaceae plant family have been identified and collected based on their study that has proven their effectiveness and uses in cardiovascular diseases. Most of the plants have an antioxidant effect, followed by anti-hyperlipidemia, vasorelaxant, antithrombotic and diuretic effect from the most available to least available studies respectively. These are the mechanisms that contribute to various cardiovascular diseases, such as heart attack, stroke, coronary heart disease, and hypertension. Further studies can be conducted on these plant species by identifying their ability and capability to be developed into a new drug or to be used as a medicinal plant in treating various cardiovascular diseases.